TECHNICAL AND ECONOMICAL PARAMETERS INFLUENCING THE PERFORMANCE AND FEASIBILITY OF ARMATRAC TRACTOR TO PERFORM PRIMARY TILLAGE AND PLANTING OPERATION IN SILTY CLAY LOAM SOIL. - Firas Salim Al-Aani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to determine the influence of performing primary tillage by moldboard plow and planting operation by four rows Gaspardo planter on some performance and economic indicators of Armatrac tractor 854e 84 hp (62kw). The system calculates and measures slippage percentage, draft force, energy requirements, and total costs for planting and tillage operation at three practical velocities and two depths. Planting operation performed at 5 and 7 cm depth under 2.90, 4.27, and 5.28 km.h-1. while ploughing operation performed at 15 and 20 cm tillage depth under 3.89, 5.28, and 6.67 km.h-1. Two factorial experiments were carried out using randomized complete block design with two factors and three replications. The results of analysis of variance showed that increases of practical velocity results in increase of slippage percentage and draft force but results in decrease of energy requirements and total costs. Furthermore, this study revealed that increases the depth of operation results in increase of slippage percentage, draft force, energy requirements, and total costs.